#TITLE_ALTERNATIVE# - KUSUMA WIJAYANTI (15304001), FITRIA
Some industry activities and influent from another smaller water mains around Citarum river basin contamining the water and sediment of the river with heavy metals. Heavy metals are one of the surface water contamination. One way to protect the quality of the river is by monitoring the concentration of contaminant. The profile of heavy metals contamination is used to know the quantity of heavy metals from the first location to the last location. Beside that, this profile will show how far the industry activities and influent from another smaller water mains around Citarum River contamining this river. This research was conducted to observe the comparison of copper, cadmium, and chromium profile inside the water and sediment of Citarum River along Dayeuhkolot-Nanjung segment. Samples were taken twice at 13 different locations with one month interval between the first and the last sampling. The weather condition was different at the first and the last sampling took place. When the first time sampling activity took place, the weather was dominated with rain. The rain had been going on for few days before the day of the first sampling took place, which caused the level of Citarum River increased up to 2 m. Different weather condition was occurred when the last sampling activity took place, which showed by the level of the river was only 0.75 metres. The heavy metal concentration in water and sediment are in the following order from highest to lowest, Cu > Cr > Cd. For almost in all locations, heavy metals concentration in sediment higher than heavy metals concentration in water. In this research, it is observed that the heavy metals concentration both in water and sediment were accumulated along the river, and it is also observed that the concentration of the heavy metals were varied between each sampling depth as seen in water analysis.